GROWTH AND SILK YIELD OF BOMBYX MORI L. DUE TO REARING IN TWIN TRAY - BASU, RITA; ROYCHOUDHURY, N.; MATHUR, S.K.; SHAMSURDIN, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1991)
Effects of a newly designed twin tray on the rearing performance of silkworm, B. mori was studied in two breeds, multivoltine Nix G and bivoltine KPG-Bx P5 in unfavourable seasons (July and August) under the climatic conditions in the plains of West Bengal. Results revealed that larval rearing in twin tray, from penultimate instar until spinning, was not found to improve any of the rearing parameters significantly (P> 0.05) in both the races and seasons compared to larvalrearing in ordinary masonary board tray (control). Further, larval duration was found to be the same for larvae reared on twin tray and control in both the races and seasons.